2009
DOI: 10.1159/000236911
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Characterization of Gene Expression Associated with Unruptured Intracranial Aneurysms

Abstract: Background: The biological mechanisms by which cerebral aneurysms emerge, enlarge and rupture are not totally understood. In the present study, we analyzed the genome-wide gene expression profile in human intracranial aneurysms using cDNA microarrays. Methods: Affymetrix HU133 Plus 2.0 microarrays were used to compare gene expression levels between human cerebral aneurismal samples and normal blood vessels. Raw data were evaluated by GeneSpring software version 9.05. Differentially expressed genes were further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…As DNA methylation is a common epigenetic modification and an important regulator of gene expression, we aimed to investigate whether gene methylation modification affected the gene expression profiles in intracranial aneurysms. 16 We used microarrays to compare the methylation levels and gene expression profiles in tissue samples from intracranial aneurysms with matched tissue samples from the superficial temporal artery. The study investigate methylation modification as a potential mechanism for the observed gene expression changes in intracranial aneurysms.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…As DNA methylation is a common epigenetic modification and an important regulator of gene expression, we aimed to investigate whether gene methylation modification affected the gene expression profiles in intracranial aneurysms. 16 We used microarrays to compare the methylation levels and gene expression profiles in tissue samples from intracranial aneurysms with matched tissue samples from the superficial temporal artery. The study investigate methylation modification as a potential mechanism for the observed gene expression changes in intracranial aneurysms.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In recent years, more and more high throughput methods were used to screen the pathogenic gene of intracranial aneurysm [10]. Lots of studies on whole genome sequencing of single nucleotide polymorphism (SNP) demonstrated different single nucleotide polymorphism loci may participate in the formation, development and rupture of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The gene chip GSE26969 was downloaded from the gene expression database Gene Expression Omnibus (GEO) (Li et al, 2009), which contained data from six intracranial arterial tissue samples formed by three normal samples and three UIAs [GPL570 (HG-U133_ Plus_2) platform with Affymetrix HU133 Plus 2.0 microarrays]. Annotation information of the chip probe was performed using Affymetrix, which contained the complete Affymetrix ATH1 (25K) chip probe.…”
Section: Affymetrix Microarray Datamentioning
confidence: 99%
“…Several high-throughput screening approaches for understanding the genetics of unruptured intracranial aneurysms (UIAs) have been conducted in recent years (Li et al, 2009). However, high-throughput screening studies that focus on functional identification of differential gene expression are rare.…”
Section: Introductionmentioning
confidence: 99%